Looking into the History of Recent Police Reforms in the USA: Critical Insights, Learning and Implications - afrin, shaharia (Journal of Governance and Administrative Reform, 2022)
Abstract The police force in the United States of America (USA) has been controversial for their execution of force and actions. This paper reviews the historical account of police reforms in the USA. The review illustrates various issues and dynamics of five significant eras of police reforms – the political era, the reform era, the community policing era, the homeland security era, and the current context. The review generates several vital insights. The concurrent socio-political factors highly influenced the police reforms initiatives. The paradigm shifts of policing towards militarization transformed the psychology of policing towards the use of excessive force. Police brutality has become part of the policing norm, and racial biases continues to shape the reform ideas. Emerging evidence shows that community policing has failed to deliver its intended outcomes, and the homeland security efforts are complicated by various local and global political factors. The evaluation of the current context informs that racial discrimination, lack of community engagement, austerity in funding, inadequate data, and excessive militarization of the police force will shape the future course of the reforms. Future interventions must be informed by adequate research and coherent ideas. This review provides policymakers and practitioners with insights into the complexity of police reforms.   Abstrak Kepolisian di Amerika Serikat (AS) telah menjadi kontroversial untuk pelaksanaan kekuatan dan tindakan mereka. Makalah ini mengulas catatan sejarah reformasi kepolisian di Amerika Serikat. Tinjauan tersebut menggambarkan berbagai isu dan dinamika lima era reformasi kepolisian yang signifikan – era politik, era reformasi, era pemolisian masyarakat, era keamanan dalam negeri, dan konteks saat ini. Tinjauan ini menghasilkan beberapa wawasan penting. Faktor sosial politik yang bersamaan sangat mempengaruhi inisiatif reformasi kepolisian. Pergeseran paradigma kepolisian ke arah militerisasi mengubah psikologi kepolisian ke arah penggunaan kekuatan yang berlebihan. Kebrutalan polisi telah menjadi bagian dari norma kepolisian, dan bias rasial terus membentuk gagasan reformasi. Bukti yang muncul menunjukkan bahwa perpolisian masyarakat telah gagal memberikan hasil yang diharapkan, dan upaya keamanan dalam negeri diperumit oleh berbagai faktor politik lokal dan global. Evaluasi konteks saat ini menginformasikan bahwa diskriminasi rasial, kurangnya keterlibatan masyarakat, penghematan dana, data yang tidak memadai, dan militerisasi kepolisian yang berlebihan akan membentuk arah reformasi di masa depan. Intervensi masa depan harus diinformasikan oleh penelitian yang memadai dan ide-ide yang koheren. Tinjauan ini memberikan para pembuat kebijakan dan praktisi wawasan tentang kompleksitas reformasi kepolisian.